Informal sustainability and adult education: towards the new construction of capability environments - Claudio Pignalberi (Firenze University Press, 2019)
The paper proposes a rereading of the guidelines and theories related to the relationship between adults and the educational-training dimension also in reference to what was emphasized in the fourth (lifelong learning) and eighth (decent work) goals of the 2030 Agenda. Adult education is now an area that requires reflections and research hypotheses to foster the definition of informal paths based on the value of practice and agency. The paper proposes, therefore, an analysis of the pedagogical categories (work, training, learning) that are necessary to cultivate capacitive environments and, through the transversal reading of the results of a focus group, it proposes points of attention and ways of working useful for the installation and the realization of a learning system for the capacitations for adults and adults of the future.   Sostenibilità informale e istruzione degli adulti: verso la costruzione di nuovi ambienti capacitanti Il contributo propone una rilettura degli indirizzi e delle teorie relative al rapporto tra adulti e dimensione educativo-formativa in riferimento a quanto sottolineato nel IV (apprendimento permanente) ed VIII (lavoro dignitoso) obiettivo dell'Agenda 2030. L'educazione degli adulti costituisce oggi un ambito che necessita di riflessioni ed ipotesi di ricerca per favorire la definizione di percorsi lifelong basati sul valore della pratica e dell'agency. Il contributo propone, dunque, un'analisi delle categorie pedagogiche (lavoro, formazione, apprendimento) che si rendono necessarie per coltivare ambienti capacitanti e, attraverso la lettura trasversale dei risultati di un focus group, propone punti di attenzione e piste di lavoro utili all'impianto ed alla realizzazione di un sistema di apprendimento alle capacitazioni per gli adulti e per gli adulti del futuro.